English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Using summation notation to rewrite the following sum with the index of summation starting at the indicated number.

(1) 6
SigmaE (5+3i) ;3(indicated number)
i=1

(2) 6
E (i^3-3) ; 0(indicated number)
i=1

Thanks in advance for guidance and help!

2006-11-24 08:30:27 · 3 answers · asked by mdetaos 3 in Science & Mathematics Mathematics

3 answers

(1)
6
Σ (5+3i) =
i=1

8
Σ (5+3(i - 2)) (i from 2 later → i in the term must decrease by 2) =
i=3

8
Σ (3i - 1))
i=3



(2)
6
Σ (i^3-3) (i from 1 earlier → i in the term must increase by 1) =
i=1

5
Σ ((i+1)^3-3)
i=0

2006-11-24 09:02:47 · answer #1 · answered by Wal C 6 · 1 0

1. Since there are six terms on the original, you must still have six terms, so change the top index to 8 (you add 2 to it since you increased the bottom index by 2).
Then change the i to (i-2) so that when i starts at 3, you get 3-2 which is what it would have been originally.
(5 + 3(i-2)) = 5 + 3i - 6 = -1 + 3i

so the formula is now that.

2. Decrease the 6 on top to 5 (since the bottom index got decreased by 1); replace i with (i+1) so that when you start at i=0 wou get what it would have been to start originally.

so it's now (i+1)^3 - 3

2006-11-24 17:01:51 · answer #2 · answered by hayharbr 7 · 1 0

Instead of summing from 1 to 6, we want to start at 3. So its going to be from 3 to 8, with everything shifted up by 2. So, to counter for that, we need to shift i down by 2 in the actual formula: so you get (sum from i=3 to 8) 5+3(i-2), or 3i-1.

Similarly, for the second one, we shift the index down by 1 in the sum, so we want to shift i up by 1 in the formula. So we get (sum from i=0 to 5) (i+1)^3 - 3 (which you could expand if you wanted to.)

2006-11-24 16:54:58 · answer #3 · answered by stephen m 4 · 1 0

fedest.com, questions and answers